Respostas
respondido por:
1
(2 - 10c^3)^2 =
(2 - 10c³)² =
(2 - 10c³)(2 - 10c³) = passo a passo
2.2 - 2(1
2.2 - 2(10c³) - (10c³)2 + 10c³(10c³)
4 - 2.10c³ -10.2c³ + 10.10c³c³
4 - 20c³ - 20c³ + 100c⁶
4 - 40c³ + 100c⁶ ( resposta)
(2 - 10c³)² =
(2 - 10c³)(2 - 10c³) = passo a passo
2.2 - 2(1
2.2 - 2(10c³) - (10c³)2 + 10c³(10c³)
4 - 2.10c³ -10.2c³ + 10.10c³c³
4 - 20c³ - 20c³ + 100c⁶
4 - 40c³ + 100c⁶ ( resposta)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás